Investigation of interface microstructure properties of AISI 316l/AISI 4140 steel couple welded by friction welding process - Unal, Engin; Karaca, Faruk; Sarsilmaz, Furkan (Gazi Univ, Fac Engineering Architecture, 2019)
In this study, AISI 316L / AISI 4140 steel couple was welded by a continuous drive friction welding machine under constant friction and forging time with three different rotational speeds, forging pressure and friction pressures respectively. SEM microscopy was implemented to determine the metallurgical changes in the region of interface regarding the rotational speed, friction and forging pressure. In addition, microhardness distribution across the interface was evaluated considering the metallurgical changes. From microstructure examinations and microhardness results, the welds which were realized under lower rotational speeds, forging pressures and friction pressures it was seen that there were unconnected regions and some defects in microstructural interface and moreover microhardness values were obtained too lower when compared to the other higher parameters. However, concerning with increasing rotational speeds, heat affected zone (HAZ) was extended and also microhardness value was considerably increased with transforming martenzite phase and resulting work hardening in the excessively deformed region.
Sürtünme kaynak yöntemi ile birleştirilmiş AISI 316L/AISI 4140 çelik çiftlerinin arayüzey mikroyapi özelliklerinin incelenmesi
Keywords: Friction welding; microstructure; AISI 316L; AISI 4140 steel